Phenol removal by newly isolated Acinetobacter baumannii strain Serdang 1 in a packed-bed column reactor - Mohamad Yadzir, Zailatul Hani; Abd. Shukor, Mohd. Yunus; Ahmad, A.; Nazir, Muhammad Shahid; Shah, S.M.U.; Abdullah, Mohd. Azmuddin (Taylor & Francis, 2016)
A newly isolated Acinetobacter baumannii strain Serdang 1 was explored for its potential in phenol remediation in batch and continuous system. An immobilization cell system has been successfully developed to remove phenol in a batch system as high as 2,000 mg/L in 12 d at a rate of 6.04 mg/L/h. Repeated use of immobilized cells as many as five cycles was shown without any loss of activity. The continuous system in a packed-bed reactor achieved 65–77% phenol removal at the rate of 38.4 mg/L/h for 200 mg/L influent, which was almost three fold higher than the batch system. Low influent flow rate at 1.5 mL/min and bed height-to-diameter ratio of 15.2 reached steady state faster than the higher flow rate, and the percentage of phenol removal was also higher.